Contextualization, conflict and ethical assessment in the incidental portraits in José Martí’s Diarios de campaña (Islas, 2024)
Introduction: In José Martí’s Diarios de campaña there are not a few incidental portraits, which have not yet been considered as a specific object of study, but as part of the overall research approaches to the Apostle's diaries. The present investigation aimed at characterizing the incidental portraits present in José Martí's Diarios de campaña.Methods: For this purpose, general research methods such as analytical-synthetic, inductive-deductive and historical-logical were used, as well as textual analysis as the main specific method. In addition, the analysis of documents and the bibliographic and documentary reviews were used to establish the background, the theoretical basis and also for the selection of the sample, which consisted of nineteen incidental portraits.Results: The present analysis proves the tracing of Martí's incidental portraits as part of his biographical writing, since they are structured on the basis of the following three features: contextualization, social conflict and ethical assessment of the portrayed.Conclusions: With this research it is intended to fill the void identified in this area of Martí's studies and, as a result, it is possible to add up the characterization and definition of the incidental portraits in José Martí's campaign diaries, as well as an extension and updating of those studies that have previously approached the subject.
Keywords: Cuba; José Martí; Campaign Diaries; incidental portrait